2020
DOI: 10.7150/jca.45548
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosomal miRNA-139-3p is a Novel Biomarker of Colorectal Cancer

Abstract: Objectives: This study investigated plasma exosomal miRNA-139-3p as a blood-based biomarker for the early diagnosis and metastasis monitoring of colorectal cancer (CRC). Patients and Methods: Exosome-rich fractions were isolated from the plasma of 80 CRC patients, and 23 controls using a kit method. We then used real-time polymerase chain reaction (RT-qPCR) to detect miR-139-3p levels in all subjects to evaluate expression levels and the predictive value of plasma exosomal miR-139-3p in CRC. We also collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…15 Moreover, decreased exosomal miR-139-3p expression in plasma of the patients with colorectal cancer has the potency to serve as a novel biomarker for the early diagnosis and metastasis monitoring. 16 Recently, more and more studies have examined the importance of circulating exosomes in PE. 17,18 However, there are few studies at present to evaluate the specific mechanism of miRNA in MSC-derived exosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Moreover, decreased exosomal miR-139-3p expression in plasma of the patients with colorectal cancer has the potency to serve as a novel biomarker for the early diagnosis and metastasis monitoring. 16 Recently, more and more studies have examined the importance of circulating exosomes in PE. 17,18 However, there are few studies at present to evaluate the specific mechanism of miRNA in MSC-derived exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a study uncovered the function of miR‐139‐5p in trophoblasts by regulating soluble fms‐like tyrosine kinase‐1 in PE 15 . Moreover, decreased exosomal miR‐139‐3p expression in plasma of the patients with colorectal cancer has the potency to serve as a novel biomarker for the early diagnosis and metastasis monitoring 16 . Recently, more and more studies have examined the importance of circulating exosomes in PE 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Screening of differential exosomal microRNAs by sequencing and qPCR showed that exosomal miR-320d could distinguish, with an area under the ROC curve (AUC) of 0.633, a diagnosis of metastatic CRC ( Tang et al, 2019 ). The expression of exosomal miR-139-3p was significantly decreased in metastatic CRC, and could facilitate a diagnosis of metastasis (AUC 0.766) ( Liu et al, 2020 ). Furthermore, the level of exosomal miR-122 increased in CRC, especially in patients with liver metastasis, and its expression could help differentiate between patients with and without liver metastasis (AUC 0.81) ( Sun et al, 2020 ).…”
Section: Methods Of Liquid Biopsymentioning
confidence: 99%
“…Of note, exosomal ncRNA has the advantage as diagnostic biomarkers since exosomes exist in various types of human body fluids such as blood, urine, saliva, which can be easily obtained in clinic. For example, the upregulation of miRNA-139-3p in plasma exosome can predict the occurrence of colorectal cancer ( Liu et al, 2020 ). In urine exosomes, the expression of miR-194-5p was significantly down-regulated in patients with autosomal dominant polycystic kidney disease ( Magayr et al, 2020 ).…”
Section: Cargos Loaded In Exosomesmentioning
confidence: 99%